Political Threads on the Fashion Stage: An Analysis of Socio-Political Influence on Indonesian Fashion Trends, 1970-2000 - Ahmad Ghazy Dananjaya (Journal of Contemporary Indonesian Art, 2025)
This study examines how fashion trends in Indonesia between 1970 and 2000 served as a direct reflection of their surrounding socio-political dynamics. Fashion is not merely an aesthetic phenomenon but a cultural artifact that actively responds to and reflects shifts in power. Using a convergent mixed-methods approach, this research integrates quantitative analysis (regression and TF-IDF on media archives) with qualitative historical analysis. The findings reveal a clear evolution: in the 1970s, fashion was politicized as an instrument of cultural nationalism by the New Order regime; the 1980s turned it into a showcase for economic development success; the 1990s transformed it into an arena for symbolic resistance amidst crisis; and the post-1998 period triggered an explosion of individual expression in the Reformation era. This study concludes that the evolution of Indonesian fashion is inextricably linked to the nation's political narrative, transitioning from a tool of control to a symbol of liberation.